(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2011)
Characteristics of airborne particulate matter (PM2.5 and PM10) and black carbon (BC) concentrations have been studied at Kalabagan and Shishumela sites along Mirpur corridor in Dhaka city. These sites are the major road junction of Mirpur corridor and can represent urban background. Both PM2.5 and PM10 fractions were collected simultaneously from both sites by using Air Metrics samplers. The samplings were done for 7 days from the 19-25 January and 5 days from 27- 31 January 2009 at Kalabagan and Shisumela sites respectively. It was found that the ambient PM2.5 and PM10 concentrations were much higher than the daily Bangladesh National Ambient Air Quality Standard. From reconstructed mass (RCM) method, it was found that about 90% of PM2.5 mass comes from anthropogenic sources like motor vehicles, diesel powered generator and biomass burning sources. Since the samplings were carried out during the wintertime, the long-range transport is also expected to contribute to increase the fine PM mass. Key words: PM10; PM2.5; BC; RCM; long-range transport DOI: http://dx.doi.org/10.3329/bjsir.v46i3.9041 BJSIR 2011; 46(3): 343-352